Free Counseling and Examination of Blood Pressure, Glucose, and Uric Acid in The Context of Unusa's Real Work Lecture in The Village Randegansari, Driyorejo District, Gresik - Wahyuni, Eka Putri; Chilmiyah, Nurul (Journal of Health Community Service, 2024)
One form of higher education's concern for the social and cultural environment (Tri Dharma Perguruan Tinggi) is through the Community Service Program (KKN). With the establishment of a harmonious relationship between Higher Education and the community, it is hoped that it can provide input for improving the quality of Higher Education needed by the community. On August 4 2023, the Work Program for Free Checking blood pressure, glucose and uric acid was carried out. Health checks were carried out on 50 people in the Kalimaya Elderly Posyandu, Randegansari Village. From the results of the examination, there were 29 people (58%) with high blood pressure, 6 people (12%) with high blood sugar levels, and 15 people (30%) with high uric acid levels. Hypertension, Gout, and Blood Sugar Disease from the results of the examinations conducted, it shows that many people still experience this disease and the cause is because people do not care and do not want to carry out health checks on health workers or independently. Health workers need to provide education to the community in the Posyandu Elderly Kalimaya Village of Randegansari regarding health checks to know and control blood pressure, blood sugar, and uric acid so that they can prevent possible diseases that will arise such as hypertension, diabetes and so on.